MARJIN PEMASARAN DAN RESIKO PEDAGANG: KASUS PENGEMBANGAN RUMPUT LAUT DI PROPINSI GORONTALO - ZULHAM, ARMEN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Intensive seaweed development program occured during fisheries revitalitation program realesed by government. The development of this commodity triggred by highly demand of seaweed raw material and it’s derivative in domestic and export markets. This article write based on the RRA survey technique on marketing marjin and trade risk face by traders on seaweed trade in Gorontalo. Responden interviewed covered the stakeholders involve in seaweed business in Gorontalo. The primary data were used to analysed the marketing marjin and trader’s risk of seaweed in Gorontalo. The traders who involved in seaweed business assume to be risk preference, due to profit oriented as long as risk oriented. The research finding indicated: the price sharing recive by each stakeholder compared the retail price in Surabaya and Manado quite preferable. Asymetric price information not occured among trade levels. Marketing marjin at each level and total marjin relatively low. This information indicated the marketing cost of seaweed more absorbed for transportation cost. As a risk preference, the trader who sold the seaweed to Manado face highly risk compared to their partner who sold sea weed to Surabaya, respectively. The active involvement of government in seaweed business need the proper planning and strategy to ignore the disappearing target.
Keywords: Seaweed, Trade, Marketing Marjin, Risk.